Exploring Cancer Patient Navigation Programs Across the Globe: A Scoping Review - Nuzulullail, Agung Subakti; Agustin, Agustin; Dudini, Amalia Khasanah Ima; Fakhriyah, Anya Bunga; Annurahman, Arif; Sarifudin, Asri Wati; Hartini, Sri (http://dharmais.co.id/, 2025)
Background: The lack of quality cancer care is still experienced by cancer patients around the world. Cancer patient navigation was introduced to address this problem by eliminating the barriers encountered by patients. However, currently, the implementation of this program in each country varies according to the country's conditions. This study aims to explore the implementation of cancer patient navigation in several countries.Methods: A Scoping review used scientific articles from four databases, including SpringerLink, ProQuest, EBSCOhost, and Wiley. The selected articles were original research articles with publication years from 2020 to 2024. Determination of research questions and keywords used the P (Problem): practice and existence of cancer patient navigators; C (Concept): cancer patient navigators; and C (Context): various countries in the world. A total of 12 selected articles were related to the implementation of cancer patient navigation in 12 different countries. The research question was